KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH ( PAD ) GUNA MENDUKUNG PELAKSANAAN OTONOMI DAERAH - Mahmudah, Henny (Jurnal Ekonomi Pembangunan, 2013)
Following writing will try to work through how relationship among accepting region taxes and region retribution to PAD'S step-up by use of approaching Error Correction Model( ECM) by use of annual data begins year 1990 until years 2010. It utilizes error correction's approaching with consideration that this model feels equal to word relationship among variable one is analyzed well that in the short term and also on a long term.Â